The influence of English subtitles in movies or listening comprehension on 8th-grade learners - Isabekova , Komilaxon Islombek qizi; Gaybullayeva , Dildora Fayzullla qizi (The Lingua Spectrum, 2026)
This study explores how English subtitles in movies affect the listening comprehension skills of 8th-grade learners. Listening is considered one of the most challenging skills for students learning English as a foreign language. Many learners find it difficult to understand spoken language due to fast speech, unfamiliar vocabulary, and different accents. The use of English subtitles can support learners by providing both visual and auditory input at the same time. In this research, students were exposed to movie clips with English subtitles during classroom activities. The results showed that subtitles helped learners recognize new words, understand sentence structures, and follow the context more easily. Moreover, students felt more confident and motivated while watching movies with subtitles. The combination of sound and text allowed learners to connect pronunciation with spelling, which improved their overall comprehension. Therefore, using English subtitles in movies can be considered an effective tool for developing listening skills in middle school learners.